African swine fever virus encodes for an E2-ubiquitin conjugating enzyme that is mono- and di-ubiquitinated and required for viral replication cycle - Ferdinando B. Freitas (Nature Portfolio, 2018)
Abstract African swine fever virus is the etiological agent of a contagious and fatal acute haemorrhagic viral disease for which there are no vaccines or therapeutic options. The ASFV encodes for a putative E2 ubiquitin conjugating enzyme (ORF I215L) that shows sequence homology with eukaryotic counterparts. In the present study, we showed that pI215L acts as an E2-ubiquitin like enzyme in a large range of pH values and temperatures, after short incubation times. Further experiments revealed that pI215L is polyubiquitinated instead of multi-mono-ubiquitinated and Cys85 residue plays an essential role in the transthioesterification reaction. In infected cells, I215L gene is transcribed from 2 hours post infection and immunoblot analysis confirmed that pI215L is expressed from 4 hpi. Immunofluorescence studies revealed that pI215L is recruited to viral factories from 8 hpi and a diffuse distribution pattern throughout the nucleus and cytoplasm. siRNA studies suggested that pI215L plays a critical role in the transcription of late viral genes and viral DNA replication. Altogether, our results emphasize the potential use of this enzyme as target for drug and vaccine development against ASF.